HBV and HCV serological monitoring among injection drugs users in opiate substitution treatment in Bosnia and Herzegovina - Sinisa Skocibusic; Marko Martinac; Jurica Arapovic; Svjetlana Grgic; Jadranka Nikolic; Dino Hasanagic; Milenko Bevanda; Jelena Ravlija (Journal of Infection in Developing Countries)
Introduction: Use of intravenous heroin carries a risk of serious medical conditions, including acquiring blood-borne infections. Therefore, hepatitis B virus (HBV) and hepatitis C virus (HCV) infection represent a threat for people who inject drugs (PWID). The objectives of this study were to determine the extent and characteristics of risk factors for acquiring HBV and HCV infection in PWID included in opiate substitution treatment in the southern part of Bosnia and Herzegovina (B&H). Methodology: The study included 120 adult PWID of both sexes who participated in opiate substitution treatment. All participants were interviewed, and their blood samples were tested for the presence of the surface hepatitis B virus antigen (HBsAg) and hepatitis C virus antibodies (anti-HCV). Prevalence data were obtained and compared to the serological status. Results: HBsAg prevalence among PWID was 0.8% (1/120), whereas seroprevalence of anti-HCV was 52.5% (63/120). PWID exposed to risk-behavior factors (such as unsafe sexual activity, serving prison sentence, and tattooing) were more frequently anti-HCV positive. Sharing drug paraphernalia was found to be the most significant risk factor. The highest predictive values for acquiring HCV-infection were attributed to PWID who used heroin for more than three years and who were unmarried. Conclusions: HBsAg prevalence among PWID is rare (0.8%), while HCV-infection (52.5%) presents an important health and social issue among PWID in B&H. Sharing drug paraphernalia and intravenous heroin use longer than three years were the most prominent risk-behavior factors among the patients we investigated.